Respuesta :

Answer: y = -9x - 9

First, you need to put the two equations into slope intercept form (y=mx+b.)

1) y= -9x + 9

2) y= -10x - 9

First take the slope of #1

m = -9x

Then take the y-intercept of #2

b = -9

Now, put it into an equation.

y = -9x - 9

Hi there!

FACTS :

The general form of a y-intercept equation is : y = mx + b

Where "m" is the slope of the line and "b" is the y-intercept.


STEPS TO ANSWER:

You want the same slope as this equation : y = 9 - 9x

This equation is the same as : y = -9x + 9

In this equation the slope is : -9


You want the same y-intercept as this equation : y = -10x - 9

In this equation the y-intercept is : -9


Your slope is -9 and your y-intercept is also -9.


This means that the equation of your new line would look like this :

y = -9x - 9


There you go! I really hope this helped, if there's anything just let me know! :)